High-strength corrosion-resistant copper heat dissipation pipe based on grain boundary engineering and preparation method thereof

CN122898764APending Publication Date: 2026-10-13SOUTH CHINA UNIV OF TECH +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611395268.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-09
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

[0004]有鉴于此,本申请实施例提供一种基于晶界工程的高强耐蚀铜散热管及其制备方法,以解决现有的铜合金管材难以兼顾强度和耐腐蚀性的技术问题

Benefits of technology

[0020]此外,对P含量进行精准控制,将其严格限定在脱氧所必需的低水平(0.003~0.01%),这一设计策略与现有技术中将P作为主要强化合金元素(通常含量>0.015%)的方案形成本质区别。低合金化程度与超低氧含量的特性,确保了合金在获得优异性能的同时,仍保持了接近纯铜的高导热性。通过将冷变形量控制在50~75%、退火温度控制在550~650℃的范围内,本申请实施例的基于晶界工程的高强耐蚀铜散热管的特殊晶界比例可达45%以上,其中Σ3孪晶界比例≥35%,与现有技术相比显著提高,这是实现软态抗拉强度(≥250MPa)与耐蚀性(腐蚀速率≤0.3mm/a)协同提升的关键微观结构基础。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122898764A_ABST
    Figure CN122898764A_ABST
Patent Text Reader

Abstract

The embodiment of the application provides a high-strength corrosion-resistant copper heat dissipation pipe based on grain boundary engineering and a preparation method thereof, wherein the high-strength corrosion-resistant copper heat dissipation pipe based on grain boundary engineering comprises the following components in percentage by mass: Sn 0.05~0.2%; Ni 0.06~0.2%; Cr 0.025~0.08%; P 0.003~0.01%; the balance is Cu and inevitable impurities, wherein the oxygen content is less than or equal to 10 ppm; the high-strength corrosion-resistant copper heat dissipation pipe based on grain boundary engineering is measured by an electron backscatter diffraction technique, and the proportion of special grain boundaries is greater than or equal to 40%, wherein the proportion of Σ3 twin grain boundaries is greater than or equal to 30%. The high-strength corrosion-resistant copper heat dissipation pipe based on grain boundary engineering and the preparation method thereof provided by the embodiment of the application realize the synergistic leap of strength and corrosion resistance, and the preparation method is stable in process and easy for industrialized production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application belongs to the field of non-ferrous metal materials technology and advanced manufacturing technology, and in particular relates to a high-strength corrosion-resistant copper heat sink based on grain boundary engineering and its preparation method. Background Technology

[0002] With the rapid development of 5G communication, artificial intelligence, and new energy vehicles, chip power density has increased significantly, placing stringent requirements on the core copper alloy tubing of heat dissipation modules such as liquid cooling plates and heat pipes. The tubing must simultaneously possess high thermal conductivity, high strength, excellent corrosion resistance, and good processing plasticity. Pure copper has excellent thermal conductivity, but its strength and corrosion resistance are poor, making it unsuitable for the long-term service requirements of high-power heat dissipation devices. Therefore, the industry generally optimizes the overall performance of copper materials through alloy modification.

[0003] Currently, copper alloys are mostly strengthened by alloying with elements such as tin, phosphorus, zinc, and nickel, with some systems adding precious metals or various trace elements. This traditional technology has many shortcomings. Alloying elements can easily be introduced into high-energy random grain boundaries, forming corrosion channels and reducing the material's resistance to intergranular corrosion and stress corrosion. Excessive alloying elements can significantly weaken the thermal conductivity of the copper matrix, and complex alloy systems are difficult to control in terms of process and have high production costs, making it difficult to balance thermal conductivity, strength, corrosion resistance, and processing economy. Summary of the Invention

[0004] In view of this, embodiments of this application provide a high-strength corrosion-resistant copper heat sink based on grain boundary engineering and its preparation method, in order to solve the technical problem that existing copper alloy tubes are difficult to balance strength and corrosion resistance.

[0005] In a first aspect, embodiments of this application provide a high-strength corrosion-resistant copper heat sink based on grain boundary engineering, comprising the following components by mass percentage: Sn 0.05~0.2%, Ni 0.06~0.2%, Cr 0.025~0.08%, P 0.003~0.01%, with the balance being Cu and unavoidable impurities, wherein the oxygen content is ≤10ppm; the high-strength corrosion-resistant copper heat sink based on grain boundary engineering, as determined by electron backscatter diffraction technology, has a special grain boundary ratio ≥40%, wherein the ratio of Σ3 twin boundaries is ≥30%.

[0006] This application employs a ternary microalloying system design with "low Sn, low Ni, and low Cr". Ni effectively reduces the stacking fault energy of the copper matrix, creating favorable conditions for subsequent grain boundary engineering and facilitating the formation of numerous annealing twins during annealing. Cr has extremely high oxygen affinity and preferentially reacts with oxygen in corrosive environments, forming a dense, stable, and highly adhesive Cr2O3 passivation film on the material surface in situ. This physically isolates the material matrix from the corrosive medium, significantly improving corrosion resistance. The P content is strictly limited to the low level necessary for deoxidation, fundamentally different from existing technologies that use P as the main strengthening alloying element, ensuring the alloy maintains near-pure copper's high thermal conductivity. The oxygen content is controlled below 10 ppm to ensure the cleanliness of the matrix, avoiding interference from oxide inclusions on grain boundary engineering and providing pure matrix conditions for the formation of high-proportion special grain boundaries.

[0007] Furthermore, the microstructure of the high-strength, corrosion-resistant copper heat sink based on grain boundary engineering is characterized by the following: as determined by electron backscatter diffraction, the proportion of special grain boundaries (CSL, Σ≤29) is ≥45%, of which the proportion of Σ3 twin boundaries is ≥35%. By optimizing the cold deformation amount and annealing process parameters, the proportion of special grain boundaries is further improved, which is significantly enhanced compared with the existing technology. This is the key microstructure basis for achieving a synergistic improvement in soft tensile strength and corrosion resistance.

[0008] Preferably, the mass ratio of Sn to Ni is (0.5~2.5):1, and the mass ratio of Ni to Cr is (2~5):1. By optimizing the element ratio, the synergistic effect of the Sn-Ni-Cr ternary microalloying system is enhanced, achieving the best balance of strength, plasticity, and corrosion resistance while maintaining high thermal conductivity.

[0009] Specifically, the grain size of the high-strength, corrosion-resistant copper heat sink based on grain boundary engineering is 20~45μm. This reasonable grain size range ensures both the strength of the material and maintains good plasticity and processing performance.

[0010] In some embodiments, the high-strength, corrosion-resistant copper heat sink based on grain boundary engineering meets at least one of the following performance requirements: soft tensile strength ≥250 MPa at room temperature, elongation ≥50%; thermal conductivity ≥380 W / (m·K); corrosion rate ≤0.3 mm / a. The synergistic achievement of these performance indicators fully demonstrates the technical advantages of this invention in composition design and grain boundary engineering control.

[0011] Secondly, embodiments of this application also provide a method for preparing a high-strength, corrosion-resistant copper heat sink based on grain boundary engineering, comprising the following steps: Provide raw materials, said raw materials comprising the components described above in the specified mass percentages; The raw materials are melted and then poured to obtain an ingot; The ingot is homogenized to obtain a homogenized sample; The homogenized sample was subjected to hot extrusion, and the extruded copper tube blank was water quenched. The water-quenched copper tube blank is then subjected to cold drawing. The cold-drawn copper tube undergoes grain boundary engineering annealing followed by rapid cooling to obtain the high-strength, corrosion-resistant copper heat sink based on grain boundary engineering. This preparation method ensures the formation of a high proportion of special grain boundary structures by precisely controlling the parameters of each process step.

[0012] In some embodiments, the cold drawing process of the water-quenched copper tube blank includes: performing multiple cold drawing processes on the water-quenched copper tube blank.

[0013] In some embodiments, the step of performing grain boundary engineering annealing on the cold-drawn copper tube and rapidly cooling it to obtain the high-strength corrosion-resistant copper heat sink based on grain boundary engineering includes performing multiple grain boundary engineering annealing processes on the cold-drawn copper tube and rapidly air-cooling or water-cooling to obtain the high-strength corrosion-resistant copper heat sink based on grain boundary engineering.

[0014] In some embodiments, the deformation of the copper tube blank after cold drawing is 50-75% in the cold drawing process. By controlling the cold working deformation within an optimal window, sufficient and uniform distortion energy is stored inside the material, providing a driving force for grain boundary migration and structural reorganization in the subsequent annealing process.

[0015] In some embodiments, the grain boundary engineering annealing treatment includes annealing at 550~650℃ for 10~25 min, followed by rapid air cooling or water cooling. This high-temperature, short-time annealing process provides sufficient activation energy at the high temperature, promoting rapid grain boundary migration and reactions, efficiently transforming high-energy random grain boundaries into low-energy Σ3 twin boundaries and their derivatives. Strict control of the holding time effectively inhibits excessive grain growth and prevents the destruction of the already formed special grain boundary structure. It achieves non-equilibrium state control of the grain boundary structure, retaining some deformed structures in the matrix where complete recrystallization has not occurred, forming a composite strengthened structure of high-density special grain boundaries and substructures.

[0016] In some embodiments, the ingot is homogenized to obtain a homogenized sample, which includes homogenizing the ingot in a box-type resistance furnace at a homogenization temperature of 850~900℃ for 2~6 hours to eliminate component segregation.

[0017] In some embodiments, the hot extrusion treatment of the homogenized sample and the water quenching of the extruded copper billet include: preheating the extrusion cylinder and die to 400-450°C, feeding the homogenized sample onto the extrusion press for extrusion, with an extrusion deformation of 75-95%, and quenching the extruded copper billet in water. Homogenization treatment eliminates compositional segregation in the as-cast structure, and rapid water quenching after hot extrusion fixes the high-temperature microstructure, laying the foundation for subsequent grain boundary engineering.

[0018] In some embodiments, melting the raw material and then casting it to obtain an ingot includes: The raw material is placed in a medium-frequency induction furnace for melting, and the temperature is raised to 1150~1250℃. After the raw material is completely melted, it is stirred evenly, and an inert gas is passed through the furnace for protection. The furnace is covered with charcoal to obtain a liquid alloy. The liquid alloy is placed in a mold and cooled using a non-vacuum casting method, with the casting temperature controlled at 1100~1200℃, to cast the ingot. The smelting process employs inert gas protection and charcoal covering to effectively prevent oxidation and ensure that the oxygen content is controlled below 10ppm.

[0019] This application provides a high-strength, corrosion-resistant copper heat sink based on grain boundary engineering and its preparation method. It employs a microalloying system with "low Sn, low Ni, and low Cr," controlling the Cr content at 0.025~0.08 wt%. Reducing the Cr content avoids the adverse effects of excessive Cr on thermal conductivity. Simultaneously, the synergistic effect of Sn and Ni lowers stacking fault energy, promoting the formation of a high proportion of twins in subsequent grain boundary engineering. Ni effectively reduces the stacking fault energy of the copper matrix, creating favorable conditions for subsequent grain boundary engineering processes. The low stacking fault energy makes it easier for the material to form a large number of annealed twins during annealing. These twin boundaries, as low-energy special grain boundaries, can pre-block dislocation movement, significantly improving material strength. Furthermore, their stable crystal structure can inhibit the intergranular penetration of corrosive media, thus significantly enhancing corrosion resistance. The scattering effect of twin boundaries on electrons is much smaller than that of ordinary grain boundaries, thus strengthening the material while maximizing the preservation of the inherent high thermal conductivity of copper alloys, achieving a balance between strength and high thermal conductivity. In addition to solid solution strengthening, the addition of Cr also has a very high oxygen affinity. In corrosive environments, Cr preferentially reacts with oxygen over the copper matrix to form a dense, stable and highly adhesive Cr2O3 passivation film on the material surface in situ. This film can physically isolate the material matrix from the corrosive medium, effectively blocking the corrosion electrochemical reaction, thereby improving the corrosion resistance of the alloy, especially its resistance to pitting corrosion and intergranular corrosion.

[0020] Furthermore, the precise control of the phosphorus (P) content, strictly limiting it to the low level necessary for deoxidation (0.003~0.01%), is fundamentally different from existing technologies that use P as the main strengthening alloying element (typically >0.015%). The low alloying degree and ultra-low oxygen content ensure that the alloy achieves excellent performance while maintaining high thermal conductivity close to that of pure copper. By controlling the cold deformation amount to 50~75% and the annealing temperature to the range of 550~650℃, the special grain boundary ratio of the high-strength corrosion-resistant copper heat sink based on grain boundary engineering in this application embodiment can reach over 45%, with the Σ3 twin boundary ratio ≥35%, significantly improved compared to existing technologies. This is the key microstructure basis for achieving a synergistic improvement in soft tensile strength (≥250MPa) and corrosion resistance (corrosion rate ≤0.3mm / a). Attached Figure Description

[0021] To more clearly illustrate the technical solutions in the embodiments of this application, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0022] Figure 1 This is a grain boundary and grain size distribution diagram of a high-strength corrosion-resistant copper heat sink based on grain boundary engineering, provided in Embodiment 2 of this application. Figure 1 Part (a) in the diagram is a schematic diagram of grain boundaries. Figure 1 Part (b) in the diagram is a grain size distribution map. Detailed Implementation

[0023] In the following description, specific details such as particular system architectures and techniques are set forth for illustrative purposes and not for limitation, in order to provide a thorough understanding of the embodiments of this application. However, those skilled in the art will understand that the embodiments of this application can also be implemented in other embodiments without these specific details. In other instances, detailed descriptions of well-known systems, apparatuses, circuits, and methods are omitted so as not to obscure the description of the embodiments of this application with unnecessary detail.

[0024] It should also be understood that the term "and / or" as used in the specification of embodiments of this application and the appended claims refers to any combination of one or more of the associated listed items and all possible combinations, and includes such combinations.

[0025] It should be noted that when a component is referred to as being "fixed to" or "set on" another component, it can be directly on or indirectly on that other component. When a component is referred to as being "connected to" another component, it can be directly connected to or indirectly connected to that other component.

[0026] It should be understood that the terms "length", "width", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inner", and "outer" indicate the orientation or positional relationship based on the orientation or positional relationship shown in the accompanying drawings. They are only for the convenience of describing the embodiments of this application and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation. Therefore, they should not be construed as limitations on the embodiments of this application.

[0027] Furthermore, in the description of the embodiments and the appended claims of this application, the terms "first," "second," "third," etc., are used only for distinguishing descriptions and should not be construed as indicating or implying relative importance.

[0028] In the description of embodiments in this application, references to "some embodiments" or "some embodiments" mean that one or more embodiments of this application include a specific feature, structure, or characteristic described in connection with that embodiment. Therefore, the phrases "in some embodiments," "in some embodiments," "in other embodiments," "in still other embodiments," etc., appearing in different parts of this specification do not necessarily refer to the same embodiments, but rather mean "one or more, but not all, embodiments," unless otherwise specifically emphasized. The terms "comprising," "including," "having," and variations thereof mean "including but not limited to," unless otherwise specifically emphasized. "A plurality" refers to two or more.

[0029] It should be noted that the meanings of the English abbreviations used in this article are as follows: Sn - Tin, P - Phosphorus, Zn - Zinc, Ni - Nickel, Ag - Silver, Pd - Palladium, Cr - Chromium, Cu - Copper.

[0030] Existing technologies typically strengthen copper materials through alloying, such as adding elements like Sn, P, Zn, and Ni. However, these methods share common drawbacks: while increasing strength, traditional strengthening techniques often introduce high-energy random grain boundaries, which may form selective corrosion channels, leading to decreased resistance to intergranular corrosion and stress corrosion cracking; the addition of excessive alloying elements significantly reduces the intrinsic thermal conductivity of copper; complex alloy systems are process-sensitive and difficult to control, and some patents contain precious metals such as Ag and Pd, resulting in high costs.

[0031] Grain boundary engineering is an emerging technology that uses thermomechanical processing to control the microstructure of materials and significantly increase the proportion of special grain boundaries with low interface energy. A high proportion of these special grain boundaries can simultaneously act as an obstacle to dislocation movement and a barrier to corrosion crack propagation, thereby synergistically improving strength and corrosion resistance. However, material composition design and processing technology are crucial prerequisites for the successful implementation of grain boundary engineering.

[0032] Related technologies disclose a copper alloy material containing 0.1–0.8% Cr and 0.01–0.5% of at least one element selected from the group consisting of Sn, P, etc., with the proportion of special grain boundaries Σ3 exceeding 20%. However, this patent uses a high Cr content (≥0.1%) as the main strengthening element and does not strictly limit the P content (up to 0.5%). While excessively high Cr and P contents can improve strength, they significantly reduce the thermal conductivity of the copper alloy, making it difficult to meet the stringent thermal conductivity requirements of high-power heat dissipation devices. Other related technologies disclose a copper-based alloy containing Ni, Sn, P, and optional Cr elements, totaling 0.01–30%. This technology requires an overly wide composition range, lacks optimization design for grain boundary engineering processes, and fails to control the proportion of special grain boundaries, making it difficult to achieve a synergistic improvement in strength and corrosion resistance. Certain elements (such as excessively high P content) can inhibit the formation of annealing twins.

[0033] Based on this, the embodiments of this application employ a Sn content of less than 0.3%, a Ni content of less than 0.2%, and Cr microalloying, while controlling trace amounts of P as a deoxidizer and strictly limiting its residual amount, and explicitly using grain boundary engineering as the core method to simultaneously improve strength and corrosion resistance. The embodiments of this application have discovered and defined a high degree of compatibility between a specific low-content Sn-Ni-Cr-P composition system and grain boundary engineering processes. By utilizing Ni to reduce stacking fault energy to promote twin formation, Cr to form a passivation film to improve corrosion resistance, and ultra-low P content to avoid inhibiting twin formation, a high-strength, corrosion-resistant copper heat sink based on grain boundary engineering and its preparation method are developed.

[0034] In a first aspect, embodiments of this application provide a high-strength corrosion-resistant copper heat sink based on grain boundary engineering, comprising the following components by mass percentage: Sn 0.05~0.2%, Ni 0.06~0.2%, Cr 0.025~0.08%, P 0.003~0.01%, with the balance being Cu and unavoidable impurities, wherein the oxygen content is ≤10ppm; the microstructure of the high-strength corrosion-resistant copper heat sink based on grain boundary engineering is characterized by the following: as determined by electron backscatter diffraction, the proportion of special grain boundaries (CSL, Σ≤29) is ≥40%, wherein the proportion of Σ3 twin boundaries is ≥30%.

[0035] This application employs a ternary microalloying system design with "low Sn, low Ni, and low Cr". Ni effectively reduces the stacking fault energy of the copper matrix, creating favorable conditions for subsequent grain boundary engineering and facilitating the formation of numerous annealing twins during annealing. Cr has extremely high oxygen affinity and preferentially reacts with oxygen in corrosive environments, forming a dense, stable, and highly adhesive Cr2O3 passivation film on the material surface in situ. This physically isolates the material matrix from the corrosive medium, significantly improving corrosion resistance. The P content is strictly limited to the low level necessary for deoxidation, fundamentally different from existing technologies that use P as the main strengthening alloying element, ensuring the alloy maintains near-pure copper's high thermal conductivity. The oxygen content is controlled below 10 ppm to ensure the cleanliness of the matrix, avoiding interference from oxide inclusions on grain boundary engineering and providing pure matrix conditions for the formation of high-proportion special grain boundaries.

[0036] It should be noted that the copper used in the embodiments of this application is oxygen-free copper, wherein the copper content in the oxygen-free copper is 99.95%, and the oxygen content is less than 10 ppm.

[0037] In some embodiments, the proportion of special grain boundaries in the high-strength corrosion-resistant copper heat sink based on grain boundary engineering is ≥45%, of which the proportion of Σ3 twin boundaries is ≥35%. By optimizing the cold deformation amount and annealing process parameters, the proportion of special grain boundaries is further improved, which is significantly enhanced compared with the prior art. This is the key microstructure basis for achieving synergistic improvement of soft tensile strength and corrosion resistance.

[0038] In some embodiments, the mass ratio of Sn to Ni is (0.5~2.5):1, and the mass ratio of Ni to Cr is (2~5):1. Specifically, the mass ratio of Sn to Ni can be 0.5:1, 0.6:1, 0.8:1, 0.9:1, 1.0:1, 1.2:1, 1.5:1, 1.6:1, 1.8:1, 2:1, 2.2:1, 2.5:1, etc., and the mass ratio of Ni to Cr can be 2:1, 2.2:1, 2.5:1, 2.6:1, 2.8:1, 3:1, 3.5:1, 3.8:1, 4:1, 4.2:1, 4.5:1, 5:1, etc. By optimizing the element ratio, the synergistic effect of the Sn-Ni-Cr ternary microalloying system is enhanced, achieving the best balance of strength, plasticity, and corrosion resistance while maintaining high thermal conductivity.

[0039] In some embodiments, the grain size of the high-strength, corrosion-resistant copper heat sink based on grain boundary engineering is 20~45μm. Specifically, the grain size can be 20μm, 25μm, 28μm, 30μm, 35μm, 38μm, 40μm, 45μm, etc. A reasonable grain size range ensures both the strength of the material and maintains good plasticity and processing performance.

[0040] In some embodiments, the high-strength, corrosion-resistant copper heat sink based on grain boundary engineering meets at least one of the following performance requirements: soft tensile strength ≥250 MPa at room temperature, elongation ≥50%; thermal conductivity ≥380 W / (m·K); corrosion rate ≤0.3 mm / a. The synergistic achievement of these performance indicators fully demonstrates the technical advantages of this invention in composition design and grain boundary engineering control.

[0041] The high-strength, corrosion-resistant copper heat sink based on grain boundary engineering provided in this application adopts a micro-alloying system of "low Sn, low Ni, and micro Cr". The Cr content is controlled at 0.025~0.08%. By reducing the Cr content, the adverse effects of excessive Cr on thermal conductivity are avoided. At the same time, the synergistic effect of Sn and Ni reduces the stacking fault energy and promotes the formation of a high proportion of twins in subsequent grain boundary engineering. Ni effectively reduces the stacking fault energy of the copper matrix, creating favorable conditions for subsequent grain boundary engineering processes. The low stacking fault energy makes it easier for the material to form a large number of annealing twins during annealing. These twin boundaries, as low-energy special grain boundaries, can pre-block dislocation movement, significantly improving the material strength. At the same time, their stable crystal structure can inhibit the intergranular penetration of corrosive media, thereby significantly enhancing corrosion resistance. The scattering effect of twin boundaries on electrons is much smaller than that of ordinary grain boundaries. Therefore, while strengthening the material, the inherent high thermal conductivity of copper alloys can be preserved to the greatest extent, achieving compatibility between toughness and high thermal conductivity. In addition to solid solution strengthening, the addition of Cr (Cr) also provides extremely high oxygen affinity. In corrosive environments, Cr preferentially reacts with oxygen over the copper matrix, forming a dense, stable, and highly adhesive Cr₂O₃ passivation film in situ on the material surface. This film physically isolates the material matrix from the corrosive medium, effectively blocking the electrochemical corrosion reaction, thereby improving the alloy's corrosion resistance, especially its resistance to pitting and intergranular corrosion. Precise control of the P (P) content, strictly limiting it to the low level necessary for deoxidation (0.003~0.01%), is fundamentally different from existing technologies that use P as the main strengthening alloying element (typically >0.015%). The low alloying degree and ultra-low oxygen content ensure that the alloy achieves excellent performance while maintaining high thermal conductivity close to that of pure copper. By controlling the cold deformation amount within 50-75% and the annealing temperature within the range of 550-650℃, the proportion of special grain boundaries in this invention can reach over 45%, with the proportion of Σ3 twin boundaries ≥35%, which is significantly improved compared to existing technologies. This is the key microstructural basis for achieving a synergistic improvement in soft tensile strength (≥250MPa) and corrosion resistance (corrosion rate ≤0.3mm / a). Strictly controlling the oxygen content below 10ppm ensures the cleanliness of the matrix, avoids interference from oxide inclusions on grain boundary engineering, and provides pure matrix conditions for the formation of a high proportion of special grain boundaries.

[0042] Secondly, embodiments of this application also provide a method for preparing a high-strength, corrosion-resistant copper heat sink based on grain boundary engineering, comprising the following steps: S10. Provide raw materials, which include the components mentioned above in the mass percentage; S20. The raw materials are melted and then poured to obtain an ingot; S30. Homogenize the ingot to obtain a homogenized sample; S40. The homogenized sample is subjected to hot extrusion treatment, and the extruded copper tube blank is water quenched. S50. The water-quenched copper tube blank is cold-drawn. S60. The cold-drawn copper tube is annealed and cooled to obtain a high-strength corrosion-resistant copper heat sink based on grain boundary engineering.

[0043] The preparation method provided in this application comprises a complete process chain: casting → homogenization → hot extrusion and water quenching → cold drawing + annealing. First, casting defects and compositional segregation are eliminated. Then, excellent solid solution microstructure is obtained through hot deformation and rapid cooling. Finally, the tube dimensions, grain size, and internal stress are precisely controlled through cold deformation and heat treatment. The resulting high-strength, corrosion-resistant copper heat sink tube, based on grain boundary engineering, has fine grains and a uniform microstructure, exhibiting high dimensional accuracy, excellent mechanical strength, and corrosion resistance. The finished product shows good consistency and is suitable for large-scale industrial production.

[0044] In some embodiments, the water-quenched copper tube blank undergoes cold drawing, including multiple cold drawing processes. In some embodiments, the cold-drawn copper tube undergoes grain boundary engineering annealing and rapid cooling to obtain a high-strength, corrosion-resistant copper heat sink based on grain boundary engineering. This includes multiple grain boundary engineering and annealing processes on the cold-drawn copper tube, followed by rapid air or water cooling to obtain a high-strength, corrosion-resistant copper heat sink based on grain boundary engineering. In some embodiments, the deformation of the cold-drawn copper tube blank is 50-75% in the cold drawing process. A combined strategy of "controlling cold deformation + high-temperature short-time annealing" is adopted to ensure the formation of a high proportion of special grain boundaries. By strictly controlling the cold working deformation within the "optimal window" of 55%-70%, sufficient and uniform distortion energy is stored within the material, providing a driving force for grain boundary migration and structural reorganization during the subsequent annealing process. The selection of this deformation range has been systematically optimized: if the deformation is too low (<55%), the stored energy is insufficient, making it difficult to drive a sufficient grain boundary reaction; if the deformation is too high (>70%), it may induce excessive texture or form unstable substructures, thus inhibiting the formation of special grain boundaries. Specifically, the cold working deformation can be 55%, 56%, 58%, 60%, 62%, 64%, 65%, 68%, 70%, etc.

[0045] In some embodiments, grain boundary engineering annealing includes annealing at 550~650℃ for 10~25 min, followed by air cooling or water cooling. Specifically, the annealing temperature can be 550℃, 560℃, 580℃, 590℃, 600℃, 620℃, 630℃, 640℃, 650℃, etc. The holding time is 10 min, 12 min, 14 min, 15 min, 16 min, 18 min, 20 min, 22 min, 25 min, etc. This high-temperature, short-time annealing process provides sufficient activation energy at a high temperature, promoting rapid grain boundary migration and reactions, efficiently transforming high-energy random grain boundaries into low-energy Σ3 twin boundaries and their derived grain boundaries. Strict control of the holding time effectively inhibits excessive grain growth and prevents the destruction of the already formed special grain boundary structure. It achieves non-equilibrium state control of the grain boundary structure, retaining some deformed structures in the matrix where complete recrystallization has not occurred, forming a composite strengthened structure of high-density special grain boundaries and substructures.

[0046] In some embodiments, the ingot is homogenized to obtain a homogenized sample, including homogenizing the ingot in a box-type resistance furnace at a homogenization temperature of 850-900℃ for 2-6 hours to eliminate compositional segregation. Specifically, the homogenization temperature can be 850℃, 860℃, 880℃, 900℃, etc., and the time can be 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, etc. Homogenizing the ingot by holding it at 850-900℃ for 2-6 hours can significantly improve the atomic diffusion rate of alloying elements, effectively eliminate casting dendritic compositional segregation, homogenize the composition inside and outside the ingot, release casting internal stress, and optimize the plasticity of the billet. Temperatures below 850℃ result in insufficient diffusion and inability to eliminate segregation; temperatures above 900℃ can easily lead to coarse grains or even overheating; holding times less than 2 hours result in residual core segregation, while holding times exceeding 6 hours result in excessive grain growth. This process window can eliminate segregation while retaining good hot working performance, preventing subsequent hot extrusion cracking, and ensuring uniform and stable pipe microstructure and mechanical properties.

[0047] In some embodiments, the homogenized sample is subjected to hot extrusion, and the extruded copper tube blank is water-quenched, including: The extrusion cylinder and die are preheated to 400-450℃. The homogenized sample is then fed into the extruder for extrusion, with an extrusion deformation of 75-95%. The extruded copper tube blank is then quenched in water. Homogenization eliminates compositional segregation in the as-cast structure, and rapid water quenching after hot extrusion fixes the high-temperature microstructure, laying the foundation for subsequent grain boundary engineering.

[0048] Specifically, the extrusion cylinder and die are preheated to 400–450°C to reduce the temperature difference between the billet and the die, preventing rapid cooling and cracking of the tube surface during extrusion and ensuring uniform metal flow. A large extrusion deformation of 75%–95% is used to fully break down the coarse grains in the cast state, achieving a refined microstructure and ensuring that alloying elements are fully dissolved in the copper matrix. Immediately after extrusion, the copper billet is water-quenched to quickly lock in the high-temperature supersaturated solid solution structure and inhibit the precipitation of harmful second-phase coarsening. This entire process ensures that the copper billet is crack-free and has excellent surface quality, while also obtaining a uniform and fine solid solution structure, significantly improving the subsequent processing performance of the tube and the strength and corrosion resistance of the finished product.

[0049] In some embodiments, melting the raw materials and then casting them to obtain an ingot includes: The raw materials are placed in a medium-frequency induction furnace for melting. The temperature is raised to 1150~1250℃. After the raw materials are completely melted, they are stirred evenly. The furnace is kept warm with inert gas and covered with charcoal to obtain a liquid alloy. The liquid alloy is placed in a mold and cooled using a non-vacuum casting method, with the casting temperature controlled at 1100~1200℃, to produce the ingot. The smelting process employs inert gas protection and charcoal covering to effectively prevent oxidation and ensure the oxygen content is controlled below 10ppm. In application, to control the content of impurity elements, a high-quality graphite crucible is selected to hold the raw materials.

[0050] The method for preparing a high-strength, corrosion-resistant copper heat sink based on grain boundary engineering provided in this application employs a combined strategy of "controlling cold deformation amount + high-temperature short-time annealing" to ensure the formation of a high proportion of special grain boundaries. By strictly controlling the cold deformation amount within the optimal window of 50-75%, sufficient and uniform distortion energy is stored within the material, providing a driving force for grain boundary migration and structural reorganization during the subsequent annealing process. High-temperature short-time annealing (550-650℃ / 10-25min) provides sufficient activation energy, promoting rapid grain boundary migration and reactions, thereby efficiently consuming high-energy random grain boundaries and transforming them into low-energy Σ3 twin boundaries and their derived grain boundaries. Strict control of the holding time effectively inhibits excessive grain growth, preventing the destruction of the already formed special grain boundary structure. The high-temperature short-time annealing process enables non-equilibrium control of the grain boundary structure, retaining some deformed structures in the matrix before complete recrystallization, forming a composite strengthened structure of high-density special grain boundaries and substructures. The fabricated high-strength, corrosion-resistant copper heat sink based on grain boundary engineering possesses high strength, high plasticity (tensile strength ≥250MPa, elongation ≥50%), high thermal conductivity (≥380W / (m·K)), and excellent corrosion resistance (corrosion rate ≤0.3mm / a). The entire process is highly compatible with traditional copper tube production, the deoxidation process is mature and stable, no precious metals are added, raw material costs are low, and the yield is high, making it suitable for large-scale industrial production.

[0051] Example Unless otherwise specified, all raw materials used in the following examples are commercially available. High-purity cathode copper has a purity of ≥99.95%, electrolytic nickel has a purity of ≥99.9%, pure tin has a purity of ≥99.9%, copper-chromium master alloy has a Cr content of 10%, and phosphorus-copper master alloy has a P content of 8%.

[0052] Example 1 This application provides a high-strength, corrosion-resistant copper heat sink based on grain boundary engineering and its preparation method, wherein the preparation method includes the following steps: S10 is made from high-purity cathode copper, electrolytic nickel, pure tin, copper-chromium master alloy, and phosphorus copper master alloy. The mass percentages of Sn, Ni, Cr, and P are 0.12%, 0.12%, 0.03%, and 0.008%, respectively. The mass ratio of Sn to Ni is 1, the mass ratio of Ni to Cr is 4, and the balance is Cu.

[0053] S20. Melt the above raw materials in a medium-frequency induction furnace, heat to 1200℃, and stir evenly after the melt is completely melted. Probe the furnace with argon gas for protection and cover the surface with charcoal. Pour the mixture into a water-cooled copper mold at 1150℃ to obtain an ingot.

[0054] S30. Place the ingot in a box-type resistance furnace and hold it at 880℃ for 4 hours to eliminate component segregation.

[0055] S40. Preheat the extrusion cylinder and die to 420°C and perform hot extrusion. The extrusion deformation is 82%. The extruded copper tube blank is immediately water-quenched.

[0056] S50. The copper tube blank is subjected to multiple cold drawing processes, with a total deformation of 62%.

[0057] S60. The copper tube after cold drawing is annealed at 620℃ for 15 minutes and then rapidly air-cooled to obtain a high-strength corrosion-resistant copper heat sink based on grain boundary engineering.

[0058] Example 2 This application provides a high-strength, corrosion-resistant copper heat sink based on grain boundary engineering and its preparation method, wherein the preparation method includes the following steps: S10 is made from high-purity cathode copper, electrolytic nickel, pure tin, copper-chromium master alloy, and phosphorus copper master alloy. The mass percentages of Sn, Ni, Cr, and P are 0.20%, 0.10%, 0.05%, and 0.005%, respectively. The mass ratios of Sn / Ni and Ni are 2, and the mass ratio of Ni / Cr is 2, with the balance being Cu.

[0059] S20. Melt the above raw materials in a medium-frequency induction furnace, heat to 1250℃, and stir evenly after the melt is completely melted. Probe the furnace with argon gas for protection and cover the surface with charcoal. Pour the mixture into a water-cooled copper mold at 1200℃ to obtain an ingot.

[0060] S30. Place the ingot in a box-type resistance furnace and hold it at 860℃ for 5 hours to eliminate component segregation.

[0061] S40. Preheat the extrusion cylinder and die to 450°C and perform hot extrusion. The extrusion deformation is 95%. The extruded copper tube blank is immediately water-quenched.

[0062] S50. The copper tube blank is subjected to multiple cold drawing processes, with a total deformation of 58%.

[0063] S60. The cold-drawn copper tube is annealed at 610℃ for 20 minutes, followed by rapid water cooling to obtain a high-strength, corrosion-resistant copper heat sink based on grain boundary engineering. Figure 1 The diagram shows the grain boundary and grain size distribution of a high-strength corrosion-resistant copper heat sink based on grain boundary engineering provided in this embodiment.

[0064] Example 3 This application provides a high-strength, corrosion-resistant copper heat sink based on grain boundary engineering and its preparation method, wherein the preparation method includes the following steps: S10 is made from high-purity cathode copper, electrolytic nickel, pure tin, copper-chromium master alloy, and phosphorus copper master alloy. The mass percentages of Sn, Ni, Cr, and P are 0.10%, 0.07%, 0.025%, and 0.010%, respectively. The mass ratio of Sn to Ni is 1.43, the mass ratio of Ni to Cr is 2.8, and the balance is Cu.

[0065] S20. Melt the above raw materials in a medium-frequency induction furnace, heat to 1175℃, and stir evenly after the melt is completely melted. Probe the furnace with argon gas for protection and cover the surface with charcoal. Pour the mixture into a water-cooled copper mold at 1125℃ to obtain an ingot.

[0066] S30. Place the ingot in a box-type resistance furnace and hold it at 850°C for 6 hours to eliminate component segregation.

[0067] S40. Preheat the extrusion cylinder and die to 420°C and perform hot extrusion. The extrusion deformation is 85%. The extruded copper tube blank is immediately water-quenched.

[0068] S50. The copper tube blank is subjected to multiple cold drawing processes, with a total deformation of 68%.

[0069] S60. The copper tube after cold drawing is annealed at 640℃ for 12 minutes and then rapidly air-cooled to obtain a high-strength corrosion-resistant copper heat sink based on grain boundary engineering.

[0070] Example 4 This application provides a high-strength, corrosion-resistant copper heat sink based on grain boundary engineering and its preparation method, wherein the preparation method includes the following steps: S10 is made from high-purity cathode copper, electrolytic nickel, pure tin, copper-chromium master alloy, and phosphorus copper master alloy. The mass percentages of Sn, Ni, Cr, and P are 0.10%, 0.20%, 0.06%, and 0.007%, respectively. The mass ratio of Sn to Ni is 0.5, the mass ratio of Ni to Cr is 3.33, and the balance is Cu.

[0071] S20. Melt the above raw materials in a medium-frequency induction furnace, heat to 1225℃, and stir evenly after the melt is completely melted. Probe the furnace with argon gas for protection and cover the surface with charcoal. Pour the mixture into a water-cooled copper mold at 1175℃ to obtain an ingot.

[0072] S30. Place the ingot in a box-type resistance furnace and hold it at 870℃ for 4 hours to eliminate component segregation.

[0073] S40. Preheat the extrusion cylinder and die to 450°C and perform hot extrusion. The extrusion deformation is 90%. The extruded copper tube blank is immediately water-quenched.

[0074] S50. The copper tube blank is subjected to multiple cold drawing processes, with a total deformation of 65%.

[0075] S60. The copper tube after cold drawing is annealed at 550℃ for 25 minutes and then rapidly water-cooled to obtain a high-strength corrosion-resistant copper heat sink based on grain boundary engineering.

[0076] Example 5 This application provides a high-strength, corrosion-resistant copper heat sink based on grain boundary engineering and its preparation method, wherein the preparation method includes the following steps: S10 is made from high-purity cathode copper, electrolytic nickel, pure tin, copper-chromium master alloy, and phosphorus copper master alloy. The mass percentages of Sn, Ni, Cr, and P are 0.10%, 0.10%, 0.045%, and 0.009%, respectively. The mass ratio of Sn to Ni is 1.67, the mass ratio of Ni to Cr is 2.22, and the balance is Cu.

[0077] S20. Melt the above raw materials in a medium-frequency induction furnace, heat to 1150℃, and stir evenly after the melt is completely melted. Probe the furnace with argon gas for protection and cover the surface with charcoal. Pour the mixture into a water-cooled copper mold at 1100℃ to obtain an ingot.

[0078] S30. Place the ingot in a box-type resistance furnace and hold it at 880℃ for 2 hours to eliminate component segregation.

[0079] S40. Preheat the extrusion cylinder and die to 400°C and perform hot extrusion. The extrusion deformation is 85%. The extruded copper tube blank is immediately water-quenched.

[0080] S50. The copper tube blank is subjected to multiple cold drawing processes, with a total deformation of 62%.

[0081] S60. The copper tube after cold drawing is annealed at 580℃ for 20 minutes and then rapidly air-cooled to obtain a high-strength corrosion-resistant copper heat sink based on grain boundary engineering.

[0082] Example 6 This application provides a high-strength, corrosion-resistant copper heat sink based on grain boundary engineering and its preparation method, wherein the preparation method includes the following steps: S10 is made from high-purity cathode copper, electrolytic nickel, pure tin, copper-chromium master alloy, and phosphorus copper master alloy. The mass percentage of Sn is 0.15%, the mass percentage of Ni is 0.20%, the mass percentage of Cr is 0.08%, and the mass percentage of P is 0.007%. The mass ratio of Sn / Ni is 0.75, the mass ratio of Ni / Cr is 2.5, and the balance is Cu.

[0083] S20. Melt the above raw materials in a medium-frequency induction furnace, heat to 1225℃, and stir evenly after the melt is completely melted. Probe the furnace with argon gas for protection and cover the surface with charcoal. Pour the mixture into a water-cooled copper mold at 1175℃ to obtain an ingot.

[0084] S30. Place the ingot in a box-type resistance furnace and hold it at 870℃ for 4 hours to eliminate component segregation.

[0085] S40. Preheat the extrusion cylinder and die to 450°C and perform hot extrusion. The extrusion deformation is 90%. The extruded copper tube blank is immediately water-quenched.

[0086] S50. The copper tube blank is subjected to multiple cold drawing processes, with a total deformation of 65%.

[0087] S60. The copper tube after cold drawing is annealed at 550℃ for 25 minutes and then rapidly water-cooled to obtain a high-strength corrosion-resistant copper heat sink based on grain boundary engineering.

[0088] Comparative Example Unless otherwise specified, all raw materials used in the following comparative examples are commercially available products. High-purity cathode copper has a purity of ≥99.95%, electrolytic nickel has a purity of ≥99.9%, pure tin has a purity of ≥99.9%, copper-chromium master alloy has a Cr content of 10%, and phosphorus-copper master alloy has a P content of 8%.

[0089] Comparative Example 1 This application provides a copper alloy tubing and a method for its preparation, wherein the preparation method includes the following steps: S10 is made from high-purity cathode copper, pure tin, copper-chromium master alloy, and phosphorus copper master alloy, wherein Sn accounts for 0.30% by mass, Cr accounts for 0.10% by mass, P accounts for 0.02% by mass, and the balance is Cu.

[0090] S20. Melt the above raw materials in a medium-frequency induction furnace, heat to 1200℃, and stir evenly after the melt is completely melted. Probe the furnace with argon gas for protection and cover the surface with charcoal. Pour the mixture into a water-cooled copper mold at 1150℃ to obtain an ingot.

[0091] S30. Place the ingot in a box-type resistance furnace and hold it at 880℃ for 4 hours to eliminate component segregation.

[0092] S40. Preheat the extrusion cylinder and die to 420°C and perform hot extrusion. The extrusion deformation is 82%. The extruded copper tube blank is immediately water-quenched.

[0093] S50. The copper tube blank is subjected to multiple cold drawing processes, with a total deformation of 62%.

[0094] S60. The copper tube after cold drawing is annealed at 620°C for 15 minutes, and then rapidly air-cooled to obtain the copper alloy tube.

[0095] Comparative Example 2 It is basically the same as Comparative Example 1, except that the content of the components is different: Sn mass ratio 0.12%, Ni mass ratio 0.08%, Cr mass ratio 0.08%, P mass ratio 0.008%, and the balance is Cu.

[0096] Comparative Example 3 It is basically the same as Comparative Example 1, except that the content of the components is different: Sn mass ratio 0.12%, Ni mass ratio 0.08%, Cr mass ratio 0.03%, P mass ratio 0.015%, and the balance is Cu.

[0097] Comparative Example 4 It is basically the same as Comparative Example 1, except that the content of the components is different: Sn mass ratio 0.4%, Ni mass ratio 0.2%, Cr mass ratio 0.03%, P mass ratio 0.02%, and the balance is Cu.

[0098] Comparative Example 5 It is basically the same as Comparative Example 1, except that the content of the components is different: Sn mass ratio 0.12%, Ni mass ratio 0.08%, Cr mass ratio 0.03%, P mass ratio 0.008%, and the balance is Cu.

[0099] Comparative Example 6 It is basically the same as Comparative Example 1, except that the content of the components is different: Sn mass ratio 0.12%, Ni mass ratio 0.08%, Cr-free and P-free mass ratio 0.008%, and the balance is Cu.

[0100] Comparative Example 7 It is basically the same as Comparative Example 1, except that the content of the components is different: Sn mass ratio is 0.3%, Ni and Cr mass ratio is 0.1%, P mass ratio is 0.02%, the balance is Cu, and the total cold drawing deformation is 40%.

[0101] Comparative Example 8 It is basically the same as Comparative Example 1, except that the content of the components is different: Sn mass ratio 0.3%, Ni and Cr excluding mass ratio 0.1%, P mass ratio 0.02%, balance Cu, and annealing temperature 400℃.

[0102] Comparative Example 9 It is basically the same as Comparative Example 1, except that the content of the components is different: Sn mass ratio 0.3%, Ni and Cr excluding mass ratio 0.1%, P mass ratio 0.02%, balance Cu, and annealing temperature 700℃.

[0103] Performance testing 1. Microstructure characterization: Electron backscatter diffraction was used to analyze the proportion of special grain boundaries (based on the lattice model of coincident positions, Σ≤29) and the proportion of Σ3 twin boundaries using crystallographic orientation analysis.

[0104] 2. Mechanical property testing: Tensile test at room temperature was conducted according to GB / T 228.1. Thermal conductivity testing: The thermal diffusivity was measured using a laser thermal conductivity meter, and the thermal conductivity was calculated based on the specific heat capacity and density. The test temperature was 25℃.

[0105] 3. Corrosion resistance test: A neutral salt spray test was conducted according to GB / T 10125. The test solution was 5% NaCl solution with a pH value of 6.5-7.2, the test temperature was 35℃, and the test time was 500h. After the test, the surface corrosion morphology was observed using an optical microscope, and the corrosion rate was calculated using the weight loss method.

[0106] The performance test results of the high-strength corrosion-resistant copper heat sink based on grain boundary engineering prepared in the above embodiments and the copper alloy tube prepared in the comparative example are shown in Table 1.

[0107] Table 1 Performance test results of the examples and comparative examples

[0108] As shown in Table 1, the high-strength corrosion-resistant copper heat sinks based on grain boundary engineering prepared in Examples 1-6 of this application all have a special grain boundary ratio of ≥45%, a Σ3 twin boundary ratio of ≥35%, a tensile strength of ≥250MPa, an elongation after fracture of ≥55%, and a thermal conductivity of ≥383W·m. -1 ·K -1 The corrosion rate is ≤0.300 mm·a. -1 It exhibits excellent overall performance and fully meets the performance requirements of the high-strength corrosion-resistant copper heat sink based on grain boundary engineering in this application.

[0109] Comparative Example 1, lacking Ni, has a higher stacking fault energy, making it difficult to form a large number of twin boundaries during annealing. The proportion of special grain boundaries is only 20.3%, and the proportion of Σ3 twin boundaries is only 16.1%, far lower than in the embodiments of this application. Due to the lack of a twin boundary strengthening mechanism, Comparative Example 1 has an elongation after fracture of only 20% and a thermal conductivity of only 300 W·m. -1 ·K -1 The corrosion rate is as high as 0.948 mm·a. -1 The three indicators are far from meeting the requirements of this invention, which fully demonstrates the irreplaceable role of Ni in reducing stacking fault energy and promoting twin boundary formation.

[0110] In Comparative Example 2, the Cr content was 0.08%, which is at the upper limit of the composition range of this application. However, the Ni / Cr mass ratio was only about 1, deviating from the preferred range of (2~5):1, resulting in the inability of Ni to fully reduce the stacking fault energy. Although the proportion of special grain boundaries (45.8%) and Σ3 twin boundaries (36.5%) met the basic requirements of this invention, the elongation after fracture was only 25%, and the thermal conductivity dropped to 320 W·m. -1 ·K -1 The corrosion rate is 0.557 mm·a. -1 The plasticity and thermal conductivity of the sample are significantly inferior to those of the embodiments in this application, indicating that the reasonable control of the element ratio has an important impact on the overall performance.

[0111] Comparative Example 3 has a P content of 0.015%, exceeding the 0.003~0.01% range of this application. This excessively high P content reduces the proportion of special grain boundaries to 30.4% and the proportion of Σ3 twin boundaries to only 24.5%, both failing to meet the requirements of this application. Furthermore, the high P content significantly increases solid solution scattering in the matrix, resulting in a thermal conductivity of only 380 W·m. -1 ·K -1 The corrosion rate increased to 0.594 mm·a. -1This indicates that strictly limiting the P content to the low level required for deoxidation is key to ensuring the alloy's high thermal conductivity and high corrosion resistance.

[0112] Comparative Example 4 has a Sn content of 0.4% and a P content of 0.020%, both exceeding the scope of this application. Although the excessively high content of alloying elements resulted in a tensile strength of 290 MPa, the elongation after fracture was only 24%, and the thermal conductivity dropped to 290 W·m. -1 ·K -1 The values ​​are all far below the requirements of this application, indicating that while exceeding the optimized range for alloy element content can improve strength, it severely damages the material's plasticity and thermal conductivity, failing to achieve synergistic optimization of multiple properties. It is noteworthy that the corrosion rate of Comparative Example 4 is 0.301 mm·a. -1 Although it barely meets the requirements of this invention, the severe deterioration of its plasticity and thermal conductivity makes it unable to meet the overall performance requirements of this invention.

[0113] Comparative Example 5 has the same composition as Example 1, but it was not subjected to the preferred grain boundary engineering annealing treatment of this invention after cold drawing. The proportion of special grain boundaries was only 40.0%, and the proportion of Σ3 twin boundaries was 31.5%, which is within the critical value required by this application. The corrosion rate was 0.440 mm·a. -1 The results are significantly higher than those in the embodiments of this application, indicating that process optimization is crucial for fully leveraging the advantages of component design and further improving corrosion resistance.

[0114] Comparative Example 6 has essentially the same composition as Example 1, the only difference being the absence of Cr, but its corrosion rate is as high as 0.998 mm·a. -1 This demonstrates the necessity of Cr addition in reducing the corrosion rate.

[0115] The total deformation of the cold-drawn material in Comparative Example 7 was 40%, which is lower than the preferred range of 50-75% in this application. The stored distortion energy was insufficient, the driving force for grain boundary migration during annealing was inadequate, the proportion of special grain boundaries was only 28.4%, and the proportion of Σ3 twin boundaries was only 22.1%, both failing to meet the requirements of this application. The corrosion rate increased to 0.488 mm·a. -1 This indicates that insufficient cold deformation will lead to a significant decrease in the grain boundary engineering effect.

[0116] The annealing temperature of Comparative Example 8 was 400℃, which is lower than the range of 550~650℃ in this application. The excessively low temperature resulted in insufficient activation energy required for grain boundary migration, with special grain boundaries accounting for only 20.3% and Σ3 twin boundaries accounting for only 16.2%, leading to a corrosion rate as high as 0.542 mm·a. -1 This indicates that when the annealing temperature is too low, the grain boundary engineering effect is extremely poor, and a sufficient proportion of low-energy special grain boundaries cannot be formed.

[0117] The annealing temperature of Comparative Example 9 was 700℃, which is higher than the upper limit of 650℃ in this application. The excessively high temperature caused excessive grain growth, which destroyed the already formed special grain boundary structure. The proportion of special grain boundaries decreased to 22.4%, and the proportion of Σ3 twin boundaries was only 17.8%. The corrosion rate increased to 0.602 mm·a. -1 This indicates that when the annealing temperature exceeds the range of this application, the grain boundary engineering effect also decreases significantly, and a high proportion of special grain boundary structures cannot be obtained.

[0118] In summary, this application successfully achieved a high-proportion twin boundary structure with a special grain boundary ratio of ≥45% and a Σ3 twin boundary ratio of ≥35% through a ternary microalloying system design of "low Sn, low Ni, and micro Cr," combined with precisely controlled cold deformation (50~75%) and a high-temperature short-time annealing process (550~650℃). The results of the comparative examples demonstrate that the introduction of Ni, low-level control of P content, precise regulation of cold deformation, and reasonable selection of annealing temperature are all necessary conditions for obtaining the aforementioned high-proportion special grain boundary structure, and none can be omitted. Based on this, the fabricated high-strength corrosion-resistant copper heat sink based on grain boundary engineering maintains high thermal conductivity (≥383 W·m). -1 ·K -1 Under the premise of achieving tensile strength (≥250MPa), elongation after fracture (≥55%), and corrosion resistance (corrosion rate ≤0.300mm·a), it achieved tensile strength (≥250MPa), elongation after fracture (≥55%), and corrosion resistance (corrosion rate ≤0.300mm·a). -1 Through synergistic optimization, it provides a high-performance, high-strength, corrosion-resistant copper heat pipe solution based on grain boundary engineering for high-reliability applications such as high-power heat dissipation modules.

[0119] In the above embodiments, the descriptions of each embodiment have different focuses. For parts that are not described in detail or recorded in a certain embodiment, please refer to the relevant descriptions of other embodiments.

[0120] The above-described embodiments are only used to illustrate the technical solutions of the embodiments of this application, and are not intended to limit them. Although the embodiments of this application have been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of this application, and should all be included within the protection scope of the embodiments of this application.

Claims

1. A high-strength, corrosion-resistant copper heat sink based on grain boundary engineering, characterized in that, The components include the following percentages by mass: Sn 0.05~0.2%; Ni 0.06~0.2%; Cr 0.025~0.08%; P 0.003~0.01%; The balance is Cu and unavoidable impurities, with an oxygen content ≤10ppm; The high-strength corrosion-resistant copper heat sink based on grain boundary engineering was determined by electron backscatter diffraction technology to have a special grain boundary ratio of ≥40%, of which the ratio of Σ3 twin boundaries is ≥30%.

2. The high-strength, corrosion-resistant copper heat sink based on grain boundary engineering as described in claim 1, characterized in that, The proportion of special grain boundaries (CSL, Σ≤29) was determined by electron backscatter diffraction technique to be ≥45%, of which the proportion of Σ3 twin boundaries was ≥35%.

3. The high-strength, corrosion-resistant copper heat sink based on grain boundary engineering as described in claim 1, characterized in that, The mass ratio of Sn to Ni is (0.5~2.5):1, and the mass ratio of Ni to Cr is (2~5):

1.

4. The high-strength, corrosion-resistant copper heat sink based on grain boundary engineering as described in claim 1, characterized in that, The grain size of the high-strength corrosion-resistant copper heat sink based on grain boundary engineering is 20~45μm.

5. The high-strength, corrosion-resistant copper heat sink based on grain boundary engineering as described in claim 1, characterized in that, The performance parameters of the high-strength corrosion-resistant copper heat sink based on grain boundary engineering meet at least one of the following: At room temperature, the soft tensile strength is ≥250 MPa, and the elongation is ≥50%. Thermal conductivity ≥380W / (m·K); Corrosion rate ≤ 0.3 mm / a.

6. A method for preparing a high-strength, corrosion-resistant copper heat sink based on grain boundary engineering, characterized in that, Includes the following steps: Provide raw materials, said raw materials comprising the components by mass percentage as described in any one of claims 1 to 5; The raw materials are melted and then poured to obtain an ingot; The ingot is homogenized to obtain a homogenized sample; The homogenized sample was subjected to hot extrusion, and the extruded copper tube blank was water quenched. The water-quenched copper tube blank is then subjected to cold drawing. The cold-drawn copper tube is subjected to grain boundary engineering annealing and rapid cooling to obtain the high-strength corrosion-resistant copper heat dissipation tube based on grain boundary engineering.

7. The preparation method according to claim 6, characterized in that, The process of cold drawing the water-quenched copper tube blank includes: performing multiple cold drawing processes on the water-quenched copper tube blank. And / or, perform grain boundary engineering annealing on the cold-drawn copper tube and rapidly cool it to obtain the high-strength corrosion-resistant copper heat sink based on grain boundary engineering, including: performing multiple grain boundary engineering annealing on the cold-drawn copper tube and rapidly air cooling or water cooling to obtain the high-strength corrosion-resistant copper heat sink based on grain boundary engineering. And / or, In the cold drawing process, the deformation of the copper tube blank after cold drawing is 50-75%.

8. The preparation method according to claim 6, characterized in that, The grain boundary engineering annealing process includes annealing at 550~650℃ for 10~25 minutes.

9. The preparation method according to claim 6, characterized in that, The ingot is homogenized to obtain a homogenized sample, which includes homogenizing the ingot in a box-type resistance furnace at a homogenization temperature of 850~900℃ for 2~6h to eliminate component segregation. And / or, The process of hot extruding the homogenized sample and water quenching the extruded copper tube blank includes: The extrusion cylinder and die are preheated to 400~450℃, and the homogenized sample is sent to the extruder for extrusion. The extrusion deformation is 75~95%, and the extruded copper tube blank is quenched in water.

10. The preparation method according to claim 6, characterized in that, The raw materials are melted and then poured to obtain an ingot, comprising: The raw material is placed in a medium-frequency induction furnace for melting, and the temperature is raised to 1150~1250℃. After the raw material is completely melted, it is stirred evenly, and an inert gas is passed through the furnace for protection. The furnace is covered with charcoal to obtain a liquid alloy. The liquid alloy is placed in a mold and cooled using a non-vacuum casting method, with the casting temperature controlled at 1100-1200℃, to cast the ingot.